The clinical potential of temsirolimus in second or later lines of treatment for metastatic renal cell carcinoma. Issue 9 (September 2013) - Stenner-Liewen, F; Grünwald, V; Greil, R; Porta, C
An impressive variety of targeted therapies has been approved for the treatment of metastatic renal cell carcinoma (mRCC). Despite promising progress, there are still unmet clinical needs. The optimal sequence of these agents in the therapeutic setting has not yet been determined. Most available data address first- and second-line therapy of clear cell RCC. The mTOR inhibitor temsirolimus has been approved for first-line treatment of mRCC, and there are new data addressing the use of temsirolimus in later therapeutic lines. Temsirolimus has discerning features compared with other currently registered drugs, such as its intravenous administration route–providing predictable bioavailability and adherence to treatment–and potential benefit in nonclear cell histologies. Here, we review the available literature on temsirolimus, with reference to data also available for everolimus, to determine its clinical potential in mRCC.